Four Arab-Israeli Wars and the Peace Process - Bailey, Sydney D. author. aut Link
XI, 522 p.
Keywords: In focusing on four major wars in the Arab-Israeli conflict from 1947 to 1979, all of them ending in agreed ceasefires, truces, or armistices, this book concentrates on the external efforts after each war to help resolve the conflict.